Keberhasilan Coronal Seal terhadap Microleakage pada Obturasi Saluran Akar Gigi 11 - Saputro, Najla; Nurdin, Denny (Bhakta Dental Journal, 2024)
Background: Root canal treatment is a treatment that aims to clean pulp tissue or microorganisms so that the root canal can be filled properly. Prevention of microleakage in the coronal part from contamination of oral fluids and microorganisms into the root canal can be achieved with a good coronal seal. Case: A 37-year-old female patient came with complaints of a broken right front upper jaw tooth caused by being hit by a door one month ago. Examination showed that tooth 11 had pulpitis irreversible asymptomatic with periodontitis apikalis symptomatic. The treatment plan is root canal treatment. Case Management: Root canal treatment begins with access opening, crown-down preparation, obturation using a single cone technique using F3 protaper guttapercha, and the coronal seal of the root canal being sealed with Universal Type Glass Ionomer cement. Conclusion: The choice of glass ionomer cement material as a root canal coronal seal against external factor contamination has quite good quality. Keywords: coronal seal, Glass Ionomer Cement, microleacage, obturation, root canal treatment